Sayyid Quṭb’s critique of Fiqh - Ushama, Thameem (IIUM Press, 2014)
Syed Quṭb’s views on Fiqh (jurisprudence) have been the subject of significant critique. This paper seeks to understand the bases of such criticisms through a qualitative content analysis of his exegesis and other writings. We begin with a brief survey of the views of scholars who have spoken in favour of and against him followed by a brief biographic profile of Quṭb. This paper focuses on Quṭb’s critique of three key issues. First, the terms Fiqh al-Awrāq (jurisprudence of papers) and Fiqh al-Ḥarakah (dynamic jurisprudence) as employed during his discourse on Fiqh are analysed. Second, his interpretation of the concept of Dār-Islām (Land of Islam) and Dār al-Ḥarb (Hostile Land) that led to criticisms by jurists are analysed through a comparison with the views of other jurists. Third, his discourse on the application of the concept of al-marḥaliyyah (stages) in jihād that caused misunderstanding among jurists is analysed in the context of a response to the need for developing dynamic jurisprudence for contemporary communities. The study endeavours to dispel ambiguities and present an objective account of Quṭb’s discourse on Fiqh.